General review of Biotechnology Role of Production Genetic Modified Organisms - Al-Hadeithi, Zeina S. M. (Journal of Pharmacology and Drug Development, 2025)
The area of Biotechnology has been both interesting and surprising from the beginning. At first, the scientists were filled with apprehension regarding the cessation of this technology's usage. It is more prudent to be cautious when making alterations to nature as the resulting outcomes remain unpredictable. Utilizing this innovative technology to enhance the nutritional value of food and combat illnesses is a logical approach. The process of creating GMOs involves extracting specific genes from one organism and inserting them into a different organism to generate modified living entities. This process usually gives the new organism specific traits that we want it to have. GMOs can be plants, animals, or enzymes that have been genetically modified. Some genetically modified organisms (GMOs) have been given permission by government agencies to be used for business and to be eaten, while others are still being reviewed by these agencies. Some GMOs are still being tested in laboratories. Genetic modification or genetic engineering of organisms can be put into groups: Green genetic engineering, also known as agro-genetic engineering, is all about creating genetically modified plants for use in farming and food production , Genetic engineering in red/yellow is used in medicine, tests for genetics, and gene therapy, as well as to make drugs like insulin and vaccines , Bacteria or yeast: These micro-organisms are created by changing their genes to make them produce specific chemicals. The chemicals they produce are used in industries to make things like medicine or other products.